Plastic filling master batch based on byproduct gypsum and preparation method of plastic filling master batch
By using plastic filled masterbatches made of industrial by-product gypsum, the problems of insufficient weather resistance and environmental pollution of woven bag products are solved, and the effect of improving product performance and resource utilization efficiency is achieved.
Patent Information
- Application Number
- CN202510052019.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-25
AI Technical Summary
The polyolefins and calcium carbonate used in existing woven bag filling masterbatches have insufficient weather resistance and environmental problems caused by mineral resource mining.
The plastic-filled masterbatch is made of industrial by-product gypsum, and the dispersion of the masterbatch and the physical properties of the product are improved by surface modification and melt blending granulation.
It improves the toughness, tensile strength and aging resistance of polyolefin products, reduces the mining demand for calcium carbonate minerals, and promotes the resource utilization of by-product gypsum.
Smart Images

Figure CN119875243A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of plastic modification and product processing, and specifically relates to a plastic filling masterbatch based on by-product gypsum and a preparation method thereof. Background Art
[0002] As a packaging material widely used in logistics, agriculture, chemical industry, construction and other fields, the market prospects of woven bags have always attracted much attention. In the context of the continuous development of the global economy and the increasing awareness of environmental protection, the woven bag market is facing new development opportunities and challenges.
[0003] First, from a global perspective, the woven bag market is huge and shows a steady growth trend, mainly due to the rapid development of industries such as logistics, agriculture, and chemicals, as well as the continuous release of demand in emerging markets.
[0004] Secondly, the improvement of environmental awareness has also brought new opportunities for the development of the woven bag market. As a reusable packaging material, woven bags have the advantages of being environmentally friendly and degradable, so they are favored by more and more companies and consumers. At the same time, with the continuous development and improvement of degradable technology, the environmental performance of woven bags will be further improved, which will help promote the expansion of the market.
[0005] At present, the filling masterbatch used in woven bags mainly uses polyolefin or polyolefin blend as the carrier and heavy calcium carbonate as the filler. It has the advantages of low cost, easy processing and good whiteness of the finished product.
[0006] However, the filling masterbatch used in woven bags also faces some challenges. On the one hand, due to its specific physical and chemical properties, polypropylene (PP) has poor weather resistance, especially prone to aging and degradation under ultraviolet rays, which limits the number of times the product can be reused; on the other hand, calcium carbonate is mainly processed from natural ores in rocks such as aragonite, calcite, chalk, limestone, marble, and travertine. In order to meet the growing demand for woven bags, a large amount of calcium carbonate filling masterbatch is needed, which in turn requires the mining of more ores, causing ecological damage and environmental pollution in mining areas. In the future, finding plastic filling masterbatch to replace calcium carbonate, reducing the demand for calcium carbonate, reducing the mining of calcium carbonate minerals, and improving the weather resistance of woven bag products are the only way for the sustainable development of the woven bag industry, and are also problems that technicians in this field need to solve urgently. Summary of the invention
[0007] In order to solve the above technical problems existing in the prior art, the present application provides a plastic filling masterbatch based on by-product gypsum and a preparation method thereof. The plastic filling masterbatch described in the present application can be used as a filling material for plastic products, such as a filling material for polypropylene and polyethylene plastic products.
[0008] This application uses industrial by-product gypsum, and by-product gypsum such as phosphogypsum can be made into filling masterbatch for use as plastic filling material. This will not only make use of the piled-up by-product gypsum resources, but also reduce the development of mineral resources such as calcium carbonate and talcum powder, and reduce the environmental burden. The use of gypsum filling masterbatch can increase the crystallization rate and β-crystal content of polyolefins. Compared with the existing calcium carbonate masterbatch, the performance of the product is improved, and the toughness and tensile strength of the product can be significantly increased, and the weather resistance such as aging resistance is improved. Moreover, through research and production, it has been found that the addition of a small amount of calcium carbonate in gypsum (accounting for 5% to 30% of the total amount of inorganic powder) can effectively improve the processing performance of the filling masterbatch, reduce the use of additives, and improve the dispersibility of the masterbatch.
[0009] Gypsum, the main component of which is calcium sulfate (CaSO4), is divided into anhydrous calcium sulfate (CaSO4), hemihydrate calcium sulfate (CaSO4·0.5H2O) and dihydrate calcium sulfate (CaSO4·2H2O) according to its different crystal water content. Studies have shown that stabilized and surface-modified anhydrous calcium sulfate can be used as a filling masterbatch to improve the impact toughness, tensile strength, bending modulus and other properties of the product, and has the potential to be used as a plastic filling material. Calcium sulfate has a wide range of sources. In addition to natural gypsum mines, a large amount of by-product gypsum is also produced in the chemical production process, such as lactic acid gypsum, desulfurized gypsum, salt gypsum, citric acid gypsum, phosphogypsum, titanium gypsum, fluorinated gypsum, etc. A large amount of industrial by-product gypsum seriously restricts the development of related enterprises. The industrial by-product gypsum can be used to replace calcium carbonate in the production of plastic filling masterbatch after harmless treatment and stabilization, which can not only improve the physical properties of plastic products, but also consume the increasing stockpiled industrial by-product gypsum.
[0010] The gypsum used in this application is by-product gypsum, which can be one by-product gypsum or a mixture of multiple different by-product gypsums. Preferably, the particle size is less than or equal to 1250 mesh (i.e., the mesh number is ≥1250 mesh); the water content is ≤0.3%, and anhydrous gypsum is preferred. The by-product gypsum used in this application is preferably by-product gypsum that has been flotated and dried, such as by-product gypsum obtained by flotation, phase change purification, morphology regulation, surface stabilization treatment, drying and calcination, and air selection and classification, which has a typical lamellar and rod structure, stable properties, and will no longer undergo hydration reaction to transform into hemihydrate gypsum and dihydrate gypsum.
[0011] In the first aspect, the present application provides a plastic filler masterbatch, which contains a modified inorganic powder with an additive coated on the surface, and a carrier resin, wherein the inorganic powder content is 70-90%, the additive content is 2-15%, and the carrier resin content is 5-25%; wherein the inorganic powder contains by-product gypsum and calcium carbonate, wherein the calcium carbonate accounts for 5-30% of the inorganic powder. The above percentages are all mass percentages.
[0012] In one group of embodiments, the plastic filling masterbatch contains modified inorganic powder with an additive coated on the surface, and a carrier resin, wherein the inorganic powder content is 75-85%, the additive content is 4-10%, and the carrier resin content is 5-20%.
[0013] Specifically, the inorganic powder content can be 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85%, the additive content can be 4, 5, 6, 7, 8, 9, 10%, and the carrier resin content can be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20%.
[0014] In one group of embodiments, the calcium carbonate accounts for 8-20% of the inorganic powder, such as 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20%. Preferably, the calcium carbonate accounts for 10-15% of the inorganic powder.
[0015] In one set of embodiments, the inorganic powder consists of by-product gypsum and calcium carbonate.
[0016] In one group of embodiments, the carrier resin is a polyolefin or a polyolefin blend, preferably, the polyolefin is selected from polyethylene and polypropylene. The polyethylene is selected from one or more of low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and high-density polyethylene (HDPE). Preferably, the polyethylene contains low-density polyethylene (LDPE), and optionally one or two selected from linear low-density polyethylene (LLDPE) and high-density polyethylene (HDPE). The polypropylene is selected from one or two of homopolymer polypropylene and random polypropylene.
[0017] Specifically, the carrier resin contains 10-100% polyethylene and 0-90% polypropylene, preferably, it contains 20-80% polyethylene, such as 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%; 20-80% polypropylene, such as 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%.
[0018] In one embodiment, the auxiliary agent comprises wax, coupling agent, and one or more selected from fatty acid, fatty acid salt, dispersant, antioxidant, and anti-ultraviolet agent. Preferably, the auxiliary agent comprises 20% to 50% wax and 10% to 40% coupling agent; more preferably, the auxiliary agent comprises 30% to 40% wax, 20% to 30% coupling agent, 0 to 40% fatty acid, 0 to 20% fatty acid salt, 0 to 40% dispersant, 0 to 1% antioxidant, and 0 to 1% anti-ultraviolet agent. Most preferably, the auxiliary agent is composed of wax, coupling agent, fatty acid and fatty acid salt, such as 30% to 40% wax, 20% to 30% coupling agent, 20% to 30% fatty acid, and 10% to 20% fatty acid salt; such as 37.5% wax, 25% coupling agent, 25% fatty acid, and 12.5% fatty acid salt.
[0019] The fatty acid includes but is not limited to one or more of stearic acid and palmitic acid, the fatty acid salt includes but is not limited to one or more of calcium stearate and zinc stearate, the wax includes but is not limited to one or more of semi-refined paraffin, polyethylene wax, cracked polyethylene wax, and Fischer-Tropsch wax, the coupling agent includes but is not limited to one or more of aluminate coupling agent, titanate coupling agent, and silane coupling agent, the dispersant includes but is not limited to one or more of vinyl bisstearamide (EBS), oleamide, and erucamide, the antioxidant includes but is not limited to one or more of phosphite antioxidants and pentaerythritol ester antioxidants, such as antioxidant 168 (tris[2.4-di-tert-butylphenyl]phosphite), antioxidant 1010 (tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] pentaerythritol ester) and similar substitutes thereof, and the anti-ultraviolet agent includes but is not limited to one or more of light stabilizer HS-508 (292), anti-ultraviolet agent 944 (hindered amine light stabilizer HS-944) and similar substitutes thereof.
[0020] In one group of embodiments, the plastic filler masterbatch is obtained by melt blending and granulating a modified inorganic powder obtained by surface activating an inorganic powder with an additive and a carrier resin, and optionally, dehydrating and drying the mixture.
[0021] In a second aspect, the present application provides a method for preparing the plastic filling masterbatch according to the first aspect, comprising the following steps:
[0022] S1. Surface modification of inorganic powder: using an additive in a high-speed mixer to perform surface activation treatment on the inorganic powder so that the surface is coated with a layer of organic matter to obtain a modified inorganic powder;
[0023] S2. Premixing the inorganic powder with the carrier resin: The modified inorganic powder obtained in step S1 is mixed with the carrier resin in a low-speed cooling mixer to obtain a mixed material;
[0024] S3 melt blending and granulation: The mixture obtained in step S2 is sent to an extruder for melt blending and granulation;
[0025] S4. Dehydration and drying of masterbatch: The masterbatch obtained in step S3 is dehydrated and dried to obtain a plastic filling masterbatch.
[0026] The preparation method of the plastic filling masterbatch described in the present application is to first perform surface activation treatment on the inorganic powder in a high-speed mixer, and then premix the modified inorganic powder with the carrier resin in a low-speed cooling mixer; on the one hand, the additive can be effectively coated on the surface of the inorganic powder to improve the compatibility of the inorganic powder with the carrier resin; on the other hand, the problem of poor dispersion of the masterbatch caused by the uneven mixing of the carrier resin and the inorganic powder can be avoided, the pressure of the extruder filter can be effectively reduced, the production speed can be increased, the total amount of materials in the high-speed mixer can be reduced, and the energy consumption can be reduced. The high-speed mixer generally refers to a mixer with a rotation speed of more than 600rpm, such as 600-1400rpm, and the low-speed cooling mixer generally refers to a mixer with a rotation speed of less than 100rpm.
[0027] In one group of embodiments, the step S1. surface modification of inorganic powder refers to: adding inorganic powder to a high-speed mixer, starting the high-speed mixer, gradually increasing the motor frequency from 0 Hz to 25 Hz, and heating at the same time (preferably electromagnetic heating) to quickly remove free water on the surface of the inorganic powder, adding an additive when the material temperature rises to 80-100°C (preferably 90-95°C), and running the high-speed mixer at a high speed of 40-60Hz (preferably 50Hz) until the material temperature reaches 110-140°C (preferably 120-130°C), and starting discharge.
[0028] Specifically, the molten additive is added to the high-speed mixer by spraying. During discharge, the mixed material is passed through an airflow cyclone screen and cooled, and the modified inorganic powder is collected by a collector for standby use. Preferably, the mesh number of the airflow cyclone screen is 250-400 mesh, more preferably 325-350 mesh; cooled to below 50°C, more preferably cooled to below 40°C; and the modified inorganic powder is collected by a cyclone collector and a bag dust collector.
[0029] In the preparation method described in the present application, in step S1, the inorganic powder is first heated to discharge free water attached to the surface of the powder; further, the inorganic powder is surface activated by adding a molten additive by spraying, and the additive is more evenly coated on the surface of the inorganic powder to form a uniform organic coating layer; finally, the surface-modified inorganic powder is passed through an air cyclone screen to break up the modified inorganic powder, which is beneficial for subsequent premixing with the carrier resin and can screen out introduced foreign matter.
[0030] In one embodiment, the step S2. premixing the inorganic powder with the carrier resin means: uniformly mixing the modified inorganic powder obtained in step S1 with the carrier resin in a low-speed cooling mixer, and naturally cooling to below 50° C., preferably below 40° C., to obtain a mixed material. The stirrer speed of the low-speed cooling mixer is 10-30 rpm.
[0031] The preparation method described in the present application premixes the modified inorganic powder with the carrier resin in a low-speed cooling mixer, which can avoid the problem of poor dispersion of the masterbatch caused by uneven mixing of the carrier resin and the inorganic powder, effectively reduce the filter pressure of the extruder, and increase the production speed.
[0032] In one set of embodiments, the step S3. melt blending and granulation refers to: feeding the mixed material obtained in step S2 into the feed port of the extruder using a forced feeding mechanism, performing melt blending, and granulating the mixture through a pelletizer.
[0033] The forced feeding mechanism has two sets of screws, horizontal and vertical, which are combined vertically at 90 degrees. The horizontal feeding screw feeds the mixed material from the low-speed cooling mixer into the vertical screw, and the vertical screw feeds the mixed material into the feed port of the extruder. The horizontal screw is a single screw with a helix angle of 30 degrees, and the vertical screw is a co-directional parallel twin screw with a helix angle of 30 degrees. The rotation speed of the forced feeding mechanism is 200-500rpm. Preferably, it is 300-400rpm.
[0034] The pelletizing by pelletizer refers to pelletizing by die surface hot cutting process; preferably, pelletizing into cylindrical particles of about 3mm*3mm. The extruder is a co-rotating twin-screw extruder or a co-rotating three-screw extruder; its screw aspect ratio is 40:1 to 52:1, and the screw speed is 800-1200rpm, preferably 900-1000rpm. The motor frequency of the pelletizer is usually 30-50Hz.
[0035] Usually, calcium carbonate masterbatch production uses a horizontal single screw feeder to feed the material, and the material enters the granulator feed port by gravity. When using this method to produce gypsum masterbatch, due to the small bulk density of gypsum, the small feeding amount, the agglomeration on the feeding screw causes uneven feeding, etc. At the same time, the gypsum has a large air content, and the granulator screw feeds a small amount of material, resulting in low production efficiency and poor material shearing and plasticization.
[0036] The preparation method described in the present application uses a twin-screw forced feeder for feeding. On the one hand, the use of a horizontal twin-screw feeder can ensure the continuous and stable feeding amount. At the same time, the use of a vertical conical twin-screw forced feeding can compress and exhaust the material, which can greatly improve the production efficiency. On the other hand, the twin-screw forced feeder has a self-cleaning function, which can effectively prevent inorganic powder and resin from clumping and sticking to the screw, resulting in feeding difficulties, thereby ensuring the continuity and stability of the production process.
[0037] In one embodiment, the step: S4. dehydration and drying of masterbatch means: dehydrating the masterbatch obtained in step S3 by centrifuge, entering a vibrating screen after dehydration, dehumidifying and drying with hot air, and optionally, entering a secondary vibrating screen for cooling to obtain a plastic filling masterbatch. Preferably, the hot air temperature is 80-150°C, more preferably 90-120°C.
[0038] Compared with the prior art, this application has the following advantages and beneficial effects:
[0039] 1) The plastic filling masterbatch of the present application uses by-product gypsum, which can replace the existing calcium carbonate masterbatch, not only realizing the resource utilization of by-product gypsum, but also reducing the development of mineral resources such as calcium carbonate and talcum powder; moreover, compared with the existing calcium carbonate masterbatch, the performance of the product is improved, and the toughness, tensile strength, aging resistance and other weather resistance of the product are significantly improved.
[0040] 2) The inorganic powder used in the plastic filling masterbatch of the present application contains by-product gypsum and calcium carbonate. Studies have found that the addition of a small amount of calcium carbonate can effectively improve the processing performance of the filling masterbatch, reduce the amount of additives used, and improve the dispersibility of the masterbatch.
[0041] 3) The preparation method of the plastic filling masterbatch described in the present application is to coat the additive on the surface of the inorganic powder in a high-speed mixer to improve the compatibility of the inorganic powder with the carrier resin, and premix the modified inorganic powder with the carrier resin in a low-speed cooling mixer to make the carrier resin and the inorganic powder mixed evenly, thereby improving the dispersibility of the masterbatch, effectively reducing the filter pressure of the extruder, increasing the production speed, and reducing energy consumption.
[0042] 4) The preparation method of the plastic filler masterbatch described in the present application is to first heat the inorganic powder in a high-speed mixer to discharge the surface water, and then spray the molten additive to make the additive more evenly coated on the surface of the inorganic powder to form a uniform organic coating layer; the modified inorganic powder is passed through an air flow cyclone screen, which can, on the one hand, break up the inorganic powder, which is beneficial to the subsequent premixing with the carrier resin, and can also screen out the introduced foreign matter.
[0043] 5) The preparation method of the plastic filling masterbatch described in the present application uses a twin-screw forced feeder to feed the mixed material into the extruder. On the one hand, it can solve the feeding difficulty caused by the low bulk density of gypsum and ensure the continuous and stable feeding amount. On the other hand, it can effectively avoid the inorganic powder and resin agglomeration and sticking to the screw, resulting in feeding difficulties, thereby ensuring the continuous and stable production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0045] Figure 1 DSC cooling curves of polypropylene and its composites.
[0046] Figure 2 This is the DSC secondary heating curve of polypropylene and its composite material.
[0047] Figure 3 Polarized microscopic images of isothermal crystallization of polypropylene and its composites.
[0048] (a) Pure PP; (b) PP / modified gypsum; (c) PP / modified talc; (d) PP / modified calcium carbonate.
[0049] Figure 4 The present invention is a schematic flow chart of an embodiment of a method for preparing a plastic filling masterbatch of the present invention.
[0050] Figure 5 It is a structural diagram of the forced feeding mechanism. DETAILED DESCRIPTION
[0051] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments. Those skilled in the art should recognize that the present invention covers all possible alternatives, improvements and equivalents within the scope of the claims.
[0052] As used in this application, the terms "comprising," "including," and "comprising" are synonymous and are inclusive or open-ended and do not exclude additional, unrecited members, elements, or method steps.
[0053]
[0013] The use of numerical ranges as endpoints herein includes all numbers and fractions subsumed within that range, as well as the recited endpoints.
[0054] The concentration values mentioned in this application include fluctuations within a certain range. For example, they can fluctuate within a corresponding accuracy range. For example, 2% can allow fluctuations within ±0.1%. For values with larger values or values that do not require too fine control, their meanings are also allowed to include larger fluctuations.
[0055] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0056] In this application, "preferred", "better", "more preferred" and "suitable" are only used to describe implementation methods or examples with better effects. It should be understood that they do not constitute a limitation on the scope of protection of this application. In this application, "optional" and "optional" mean that they are optional, that is, they refer to any one of the two parallel schemes of "yes" or "no". If multiple "optional" and "optional" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" and "optional" is independent of each other.
[0057] Example 1 Nucleation effect of gypsum on polyolefins
[0058] Taking PP as an example, the difference between the nucleating agent effect of gypsum on polyolefins and that of talc and calcium carbonate was explored.
[0059] DSC tests were performed on pure PP, PP containing 20% modified gypsum, PP containing 20% modified talc, and PP containing 20% modified calcium carbonate. The temperature was first raised to eliminate the thermal history, and then the cooling and second heating DSC curves were recorded. Figure 1-Figure 2 shown.
[0060] from Figure 1 It can be found that the cooling crystallization exothermic peaks of pure PP, PP containing 20% modified gypsum, PP containing 20% modified talc and PP containing 20% modified calcium carbonate are 111.7℃, 119.0℃, 122.3℃ and 115.3℃ respectively. As we all know, talc is a good nucleating agent, which can promote PP nucleation and greatly increase the crystallization temperature of PP. The effect of gypsum on the crystallization temperature of PP is second only to talc, while the crystallization temperature of PP filled with calcium carbonate is only increased by 3.6℃, and the effect of nucleating agent is not obvious.
[0061] from Figure 2 It can be seen that the melting endothermic peaks of pure PP, PP containing 20% modified gypsum, PP containing 20% modified talc, and PP containing 20% modified calcium carbonate appear at 169.7°C, 168.0°C, 169.3°C, and 169.3°C, respectively. It can be seen that although talc increases the crystallization temperature of PP, the melting point of the crystals generated is basically the same as that of pure PP, indicating that the crystal form has not changed and is still α crystal; while calcium carbonate has a weak nucleation effect on PP, and the melting point of the crystals formed is consistent with that of pure PP and talc-filled PP, indicating that the crystal type is consistent with that of pure PP, which is α crystal.
[0062] Figure 3The isothermal crystallization images of pure PP, PP containing 1.0% modified gypsum, PP containing 1.0% modified talc, and PP containing 1.0% modified calcium carbonate at 130°C are shown in Figure 1. Generally, the crystallization product of PP during natural cooling is mainly α-crystal, with a small number of crystals, large crystal size, and clear crystal interface. Figure 3 (a), cracks tend to extend along the weaker grain boundaries, eventually leading to material failure, so homopolymer PP usually has poor toughness; while for PP composites filled with modified gypsum, a large number of crystal nuclei are generated during the cooling crystallization process due to the nucleating agent effect of gypsum, the crystals become smaller and the grain boundaries become blurred, such as Figure 3 (b) Meanwhile, gypsum promotes the production of more β crystals, which improves the rigidity and toughness of the modified gypsum-filled PP composites. Figure 3 (c) shows the isothermal crystallization image of modified talc-filled PP. It can be seen that under the efficient nucleation effect of talc, a large number of crystal nuclei are formed during the crystallization of modified talc-filled PP, making the PP crystals smaller and the crystallinity higher. Therefore, the rigidity of the talc-filled PP composite material is improved. Figure 3 (d) shows the isothermal crystallization image of modified calcium carbonate filled PP. Since calcium carbonate has almost no nucleation effect on PP, the morphology and size of the formed crystals are basically consistent with those of pure PP.
[0063] Example 2 Preparation of plastic filling masterbatch based on by-product gypsum + calcium carbonate and performance testing
[0064] The raw material formula of plastic filling masterbatch is as follows:
[0065] Table 1 Filling masterbatch formula (%)
[0066] Serial number Material Name Example 2-1 Example 2-2 1 PE 5 13 2 PP powder 12 4 3 plaster 67.5 67.5 4 Calcium carbonate 7.5 7.5 5 Stearic acid 2 2 6 Zinc stearate 1 1 7 PE wax 3 3 8 Aluminate coupling agent 2 2
[0067] Preparation of plastic filling masterbatch:
[0068] S1. Surface modification of by-product gypsum and calcium carbonate
[0069] The by-product gypsum and calcium carbonate are put into the SHR-400 high-speed mixer, and the motor is started. The motor frequency is gradually increased from 0Hz to 25Hz, and the motor is operated at a low speed, and electromagnetic heating is started; when the material temperature rises to 90-95°C, the additive melted in the additive melting tank is sprayed into the high-speed mixer within 2 minutes, and the high-speed mixer is operated at a high speed of 50Hz and mixed for another 5 minutes. The material temperature rises to 120-130°C, and the discharge valve is started. The mixed material passes through a 325-mesh air cyclone screen and is cooled to 40°C. After being collected by a cyclone collector and a bag dust collector, it enters a powder bin for standby use, which is the modified by-product gypsum and calcium carbonate powder.
[0070] S2. Premixing of modified byproduct gypsum and calcium carbonate powder with carrier resin
[0071] The carrier resin (PE and PP powders) and the modified by-product gypsum and calcium carbonate powders obtained in step S1 are uniformly mixed in a cold mixing pot, and naturally cooled to 40° C. to obtain a mixed material.
[0072] S3. Melt blending and granulation
[0073] The mixed material obtained in step S2 is fed into a co-rotating three-screw granulator through a granulator feeding system for granulation.
[0074] Feeding system for Figure 5 The forced feeder shown has two sets of screws, horizontal and vertical, which are combined vertically at 90 degrees. The horizontal feeding screw is a single screw with a helix angle of 30 degrees, which feeds the mixed material from the cold mixer to the vertical feeding screw. The vertical feeding screw is a co-directional parallel twin screw with a helix angle of 30 degrees, which feeds the mixed material into the extruder feed port. The feeding system speed is 307rpm.
[0075] The extruder is a co-rotating three-screw extruder, and the mixed material is melt blended, extruded and pelletized in the extruder. The granulation process of the co-rotating three-screw extruder is set as follows: barrel zone 170°C, barrel zone 2 175°C, barrel zone 3 180°C, barrel zone 4 185°C, barrel zone 5 185°C, barrel zone 6 185°C, barrel zone 7 185°C, barrel zone 8 180°C, barrel zone 9 170°C, barrel zone 10 160°C, main engine speed 972rpm, current 148A, net pressure 3.7-4.0MPa, pelletizer motor frequency 30-50Hz.
[0076] S4. Dehydration and drying of masterbatch
[0077] The masterbatch obtained in step S3 is dehydrated by a centrifuge and then enters a vibrating screen for hot air dehumidification and drying at a dehumidification temperature of 100° C., and then enters a secondary vibrating screen for cooling to obtain a plastic filling masterbatch.
[0078] Performance test of plastic filling masterbatch:
[0079] The filler masterbatch prepared in Example 2-1 was tested according to QB / T 1126-2021 polyolefin filler masterbatch, and the test results are shown in Table 2. The carrier resin used in the test of mechanical property retention rate is polypropylene K8003.
[0080] Table 2 Test results of filling masterbatch in Example 2-1
[0081]
[0082] The filler masterbatch prepared in Example 2-2 was tested according to QB / T 1126-2021 polyolefin filler masterbatch, and the test results are shown in Table 3. The carrier resin used in the test of mechanical property retention rate is high-density polyethylene HD5420GA.
[0083] Table 3 Test results of filling masterbatch in Example 2-2
[0084]
[0085] Performance test of filler masterbatch for wire drawing:
[0086] The masterbatch obtained in Example 2-1 was used for high-speed wire drawing of braided belts. The proportions were shown in Table 4. The test results of the mechanical properties of the obtained flat wires were shown in Table 5.
[0087] Table 4 Example 2-1 Filling Masterbatch Drawing Test Formula
[0088] raw materials PP T03 First level return material Ton bag return Example 2-1 Masterbatch Brightener Dosage 77.67% 9.71% 4.85% 7.77% 0.015%
[0089] Table 5 Performance comparison of flat yarn produced by filling masterbatch and calcium carbonate masterbatch in Example 2-1
[0090] Serial number index Calcium carbonate masterbatch comparison sample index requirements Example 2-1 Masterbatch test sample 1 Wire width, mm 2.36 2.36 2 Single yarn weight, g / 10m 0.94±0.03 0.95 3 Single wire tension, N ≥40 47.01 4 Elongation at break, % ≥20 21.12
[0091] The masterbatch obtained in Example 2-2 was used for the production of PE blow molded pallets. The production ratio is shown in Table 6. The obtained pallets were subjected to performance tests according to GB / T15234-94. The results are shown in Table 7.
[0092] Table 6 Example 2-2 Filling masterbatch test PE pallet production formula
[0093]
[0094]
[0095] Table 7 Performance test results of PE pallets obtained by filling masterbatch production in Example 2-2
[0096]
[0097] The plastic filling masterbatch of this embodiment is added in a ratio of 5% to 10% to produce HDPE blow-molded pallets with a specification of 1200mm*1200mm, a dynamic load of 2 tons, and a static load of 6 tons. The rigidity of the product is improved, and the weight of the product can be reduced from 33kg to 31.5kg~32kg while meeting the product performance requirements, which can effectively reduce product costs.
[0098] Example 3 Preparation of plastic filler masterbatch with different inorganic powder contents and performance testing
[0099] The raw material formula of plastic filling masterbatch is as follows (2000 mesh calcium carbonate masterbatch is a high-end product sold on the market. Compared with low mesh calcium carbonate masterbatch, it has better performance and higher price):
[0100] Table 8 Plastic filling masterbatch formula
[0101]
[0102]
[0103] Preparation of plastic filling masterbatch:
[0104] S1. Surface modification of inorganic powders
[0105] Put the inorganic powder into the SHR-400 high-speed mixer, start the motor, gradually increase the motor frequency from 0Hz to 25Hz, run at low speed, and start electromagnetic heating; when the material temperature rises to 90-95℃, spray the additives melted in the additive melting tank into the high-speed mixer within 2 minutes, make the high-speed mixer run at 50Hz and mix for another 5 minutes, the material temperature rises to 120-130℃, start the discharge valve, pass the mixed material through a 325-mesh air cyclone screen and cool to 40℃, collect it by a cyclone collector and a bag dust collector, and then put it into the powder bin for standby use, which is the modified gypsum and calcium carbonate powder.
[0106] S2. Premixing of modified gypsum and calcium carbonate powder with carrier resin
[0107] The carrier resin, the modified gypsum obtained in step S1 and the calcium carbonate powder are mixed evenly in a cold mixing pot, and naturally cooled to 40° C. to obtain a mixed material.
[0108] S3. Melt blending and granulation
[0109] The mixed material obtained in step S2 is fed into a co-rotating three-screw granulator through a granulator feeding system for granulation.
[0110] Feeding system for Figure 5 The forced feeder shown has two sets of screws, horizontal and vertical, which are combined vertically at 90 degrees. The horizontal feeding screw is a single screw with a helix angle of 30 degrees, which feeds the mixed material from the cold mixer to the vertical feeding screw. The vertical feeding screw is a co-directional parallel twin screw with a helix angle of 30 degrees, which feeds the mixed material into the extruder feed port. The feeding system speed is 307rpm.
[0111] The extruder is a co-rotating three-screw extruder, and the mixed material is melt blended, extruded and pelletized, and cooled in the extruder to obtain the filling masterbatch. The granulation process of the co-rotating three-screw extruder is set as follows: barrel zone 170°C, barrel zone 2 175°C, barrel zone 3 180°C, barrel zone 4 185°C, barrel zone 5 185°C, barrel zone 6 185°C, barrel zone 7 185°C, barrel zone 8 180°C, barrel zone 9 170°C, barrel zone 10 160°C, main engine speed 972rpm, current 148A, net pressure 3.7-4.0MPa, pelletizer motor frequency 30-50Hz.
[0112] S4. Dehydration and drying of masterbatch
[0113] The masterbatch obtained in step S3 is dehydrated in a centrifuge along with water flow, and the dehydrated particles enter a vibrating screen, on which a hot air blower is installed for dehumidification, and the dehumidification temperature is about 100° C. After dehumidification, the particles enter a secondary vibrating screen for cooling, and finally enter a finished product silo.
[0114] Performance test of plastic filling masterbatch:
[0115] Referring to the detection method for masterbatch in the current calcium carbonate and talc filler masterbatch industry standard QB / T 1126-2021 "Polyolefin Filler Masterbatch", the basic physical properties of gypsum filler masterbatch were tested, and the results are shown in Table 9.
[0116] Table 9 Basic physical properties test results of filling masterbatch
[0117]
[0118] The injection molding specimen is calculated based on an inorganic powder content of 20%. 500g of filler masterbatch is taken and mixed with the resin. The resin dosage calculation formula is as follows:
[0119]
[0120] Where:
[0121] W is the amount of resin used, in g;
[0122] Wm is the amount of masterbatch, unit: g;
[0123] Y is the content of inorganic powder in the masterbatch.
[0124] The mechanical properties of the injection-molded specimens of the resin raw material and the masterbatch mixture were tested, and the results are shown in Table 10.
[0125] Table 10 Mechanical properties of resin and masterbatch mixture
[0126]
[0127]
[0128] According to the calculation method of physical property retention rate in QB / T 1126-2021, the physical property retention rate of HDPE 5420 filled with gypsum masterbatch is shown in Table 11.
[0129] Table 11 Mechanical property retention rate of HDPE 5420 filled with gypsum masterbatch
[0130]
[0131] The results show that:
[0132] 1. With the increase of gypsum content, the proportion of carrier resin and additives in the masterbatch decreases, and the reinforcing effect of gypsum masterbatch on HDPE is greatly improved.
[0133] 2. The tensile strength and flexural modulus of HDPE filled with gypsum masterbatch are higher than those of calcium carbonate masterbatch, indicating that gypsum masterbatch has a good reinforcing effect on HDPE.
[0134] 3. The addition of LLDPE 6201RQ can effectively improve the melt mass flow rate (melt index, MFR) of the masterbatch, which helps to improve the processing performance and dispersibility of the masterbatch.
[0135] The examples of the present application show that the reinforcing and toughening effects of gypsum filling masterbatch on HDPE are much higher than those of traditional calcium carbonate filling masterbatch. Products prepared by filling HDPE with the gypsum filling masterbatch provided by the present invention, including but not limited to PE blow molding and injection molding pallets, turnover boxes, extruded pipes and other products, can improve the product's anti-deformation, anti-drop and other properties under the premise of the same addition ratio as when using calcium carbonate filling masterbatch, thereby improving the product performance; or under the premise of achieving the same product indicators, more gypsum filling masterbatch can be added to reduce product costs.
[0136] In the description of this specification, the description with reference to the terms "a specific embodiment", "a set of embodiments", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0137] The protection scope of the present application is not limited to the above-mentioned embodiments. Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the scope and spirit of the present invention. If these changes and modifications fall within the scope of the claims of the present application and their equivalents, the intention of the present application also includes these changes and modifications.
Claims
1. A plastic filling masterbatch, characterized in that: Contains modified inorganic powder with an additive coated on the surface, and carrier resin, wherein the inorganic powder content is 70-90%, the additive content is 2-15%, and the carrier resin content is 5-25%; the inorganic powder contains by-product gypsum and calcium carbonate, and the calcium carbonate accounts for 5-30% of the inorganic powder.
2. The plastic filling masterbatch according to claim 1, characterized in that: The content of inorganic powder is 75-85%, the content of auxiliary agent is 4-10%, and the content of carrier resin is 5-20%.
3. The plastic filling masterbatch according to claim 1 or 2, characterized in that: The calcium carbonate accounts for 8-20% of the inorganic powder; preferably, the inorganic powder consists of by-product gypsum and calcium carbonate.
4. The plastic filling masterbatch according to claim 1 or 2, characterized in that: The carrier resin is a polyolefin or a polyolefin blend; preferably, the polyolefin is selected from polyethylene and polypropylene; More preferably, the polyethylene is selected from one or more of low-density polyethylene, linear low-density polyethylene, and high-density polyethylene; and the polypropylene is selected from one or two of homopolypropylene and random polypropylene.
5. The plastic filling masterbatch according to claim 1 or 2, characterized in that: The auxiliary agent comprises wax, coupling agent, and one or more selected from fatty acid, fatty acid salt, dispersant, antioxidant, and anti-ultraviolet agent; Preferably, the auxiliary agent comprises 30% to 50% wax and 10% to 40% coupling agent; More preferably, the auxiliary agent comprises 30% to 40% wax, 20% to 30% coupling agent, 0% to 40% fatty acid, 0% to 20% fatty acid salt, 0% to 40% dispersant, 0% to 1% antioxidant, and 0% to 1% anti-ultraviolet agent; Most preferably, the auxiliary agent is composed of 30% to 40% wax, 20% to 30% coupling agent, 20% to 30% fatty acid, and 10% to 20% fatty acid salt.
6. The plastic filling masterbatch according to claim 5, characterized in that: The fatty acid includes one or more of stearic acid and palmitic acid, the fatty acid salt includes one or more of calcium stearate and zinc stearate, the wax includes one or more of semi-refined paraffin, polyethylene wax, cracked polyethylene wax, and Fischer-Tropsch wax, the coupling agent includes one or more of aluminate coupling agent, titanate coupling agent, and silane coupling agent, the dispersant includes one or more of vinyl bisstearamide, oleamide, and erucamide, the antioxidant includes one or more of phosphite antioxidants and pentaerythritol ester antioxidants, and the anti-ultraviolet agent includes one or more of light stabilizer HS-508 (292), anti-ultraviolet agent 944, and similar substitutes thereof.
7. The plastic filling masterbatch according to any one of claims 1 to 6, characterized in that: The modified inorganic powder is obtained by surface activating the inorganic powder with an auxiliary agent, melting and blending with a carrier resin to form granules, and optionally dehydrating and drying.
8. The method for preparing a plastic filling masterbatch according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Surface modification of inorganic powder: using an additive in a high-speed mixer to perform surface activation treatment on the inorganic powder so that the surface is coated with a layer of organic matter to obtain a modified inorganic powder; S2. Premixing the inorganic powder with the carrier resin: The modified inorganic powder obtained in step S1 is mixed with the carrier resin in a low-speed cooling mixer to obtain a mixed material; S3 melt blending and granulation: The mixture obtained in step S2 is sent to an extruder for melt blending and granulation; S4. Dehydration and drying of masterbatch: The masterbatch obtained in step S3 is dehydrated and dried to obtain a plastic filling masterbatch.
9. The preparation method according to claim 8, characterized in that: The step S1 refers to adding inorganic powder into a high-speed mixer, starting the high-speed mixer, gradually increasing the motor frequency from 0 Hz to 25 Hz, and heating at the same time, adding an additive when the material temperature rises to 80-100° C., making the high-speed mixer run at a high speed of 40-60 Hz until the material temperature reaches 110-140° C., and starting the discharge; preferably, adding an additive when the material temperature rises to 90-95° C., making the high-speed mixer run at a high speed of 50 Hz until the material temperature reaches 120-130° C., and starting the discharge.
10. The preparation method according to claim 9, characterized in that: The molten additives are added to the high-speed mixer by spraying.
11. The preparation method according to claim 9, characterized in that: During discharge, the mixed material is passed through an airflow cyclone screen and cooled, and the modified inorganic powder is collected by a collector for later use; preferably, the mesh size of the airflow cyclone screen is 250-400 mesh, cooled to below 50°C, and the modified inorganic powder is collected by a cyclone collector and a bag dust collector.
12. The preparation method according to any one of claims 8 to 11, characterized in that: The step S2 refers to: uniformly mixing the modified inorganic powder obtained in step S1 with the carrier resin in a low-speed cooling mixer, and naturally cooling to below 50° C. to obtain a mixed material; preferably, the stirrer speed of the low-speed cooling mixer is 10-30 rpm.
13. The preparation method according to any one of claims 8 to 12, characterized in that: The step S3 refers to: feeding the mixed material obtained in step S2 into the feed port of the extruder by using a forced feeding mechanism, performing melt blending, and granulating the mixed material by a pelletizer.
14. The preparation method according to claim 13, characterized in that: The forced feeding mechanism has two sets of screws, horizontal and vertical, which are combined vertically at 90 degrees. The horizontal feeding screw feeds the mixed material from the low-speed cooling mixer into the vertical screw, and the vertical screw feeds the mixed material into the feed port of the extruder; preferably, the horizontal screw is a single screw with a helix angle of 30 degrees, and the vertical screw is a co-directional parallel twin screw with a helix angle of 30 degrees. The rotation speed of the forced feeding mechanism is 200-500rpm.
15. The preparation method according to claim 13 or 14, characterized in that: The extruder is a co-rotating twin-screw extruder or a co-rotating three-screw extruder; the pelletizing by a pelletizer refers to pelletizing by a die surface hot cutting process; Preferably, the extruder has a screw aspect ratio of 40:1 to 52:1, and a screw speed of 800-1200 rpm; the pellets are cut into cylindrical pellets of 3 mm*3 mm.
16. The preparation method according to any one of claims 8 to 15, characterized in that: The step S4 refers to: dehydrating the masterbatch obtained in step S3 by a centrifuge, entering a vibrating screen after dehydration, dehumidifying and drying with hot air, and optionally, entering a secondary vibrating screen for cooling to obtain a plastic filling masterbatch; preferably, the hot air temperature is 80-150°C.
Citation Information
Patent Citations
A High-Filling Oxidative Degradable Polymer Packaging Material and Its Preparation Method
CN102295793A
Polyolefin breathable masterbatch, and preparation method thereof
CN103160007A
Method for preparing light general plastic composite material by adding bulk industrial solid wastes
CN104356505A
Filler for PVC production and preparation method thereof
CN105331011A
Electric power tube and production method thereof
CN107163396A